ANTECEDENT CUSTOMER ENGAGEMENT DAN CONCEQUENCE TERHADAP BUSINESS PERFORMANCE (SUATU KAJIAN TEORITIS PADA BISNIS JASA) - Saparso, Saparso (Manajemen Bisnis Kompetensi, 2016)
This paper discusses the concept of the development of consumer engagement, in the era of globalization will increasingly play a role, because the pressure from competitors requires companies to invest more time and resources to strengthen marketing. Marketing theory past few decades has shifted along with the emergence of virtual marketing. ExploitÃ‚Âing social media caused by the development of information technology also accelerates the change. Customer behavior also changes with the new media, the offender business also must change to be more creatively capture opportunities. Creativity needs to be done to increase consumer engagement is a very important thing to do, so that producers and consumers relationship is maintained. This concept is an approach to building a portfolio of customers and connect with customers across manufacturers. The article also looks more closely related to the ability of the process of marketing, customer engagement and comÃ‚Âmercialization. Another approach of this concept is to improve customer satisfaction and loyalty, which leads to a commitment to spread the word of mouth is positive. Involvement revival will significantly improve the company's performance.Keywords: customer base, engagement, business performance